Service Quality and Customer Loyalty on Customer Satisfaction at a Hotel - Sjukriana, Juke; Falaq, Muhammad (Prasetiya Mulya Publishing, 2023)
Company Hotel Salak Express is currently experiencing very rapid development in line with the needs of society in various fields of life. To be able to meet people's needs, good service is needed in order to create loyalty for customers which will affect the company itself. At this study, the researcher aims to determine the effect of service quality and customer loyalty on customer satisfaction. The population in this study were 70 consumers of hotel service users. The data collection method was done through a questionnaire. The research method is quantitative. The data used in this study are primary data. Data collection was carried out using a questionnaire. Analysis using Multiple Regression with testing using SPSS.